Extracellular matrix remodeling fibroblasts govern the tumor microenvironment disparity between adenomatous lesions and adenocarcinoma in gallbladder - Ma, Chuhan; Hu, Huixin; Li, Hanrong; Han, Bing; Lv, Chao; Tian, Yu (Frontiers in Immunology, 2025)
IntroductionGallbladder cancer (GBC) is a highly lethal cancer with a poor prognosis. The adenoma-carcinoma sequence is a recognized model for GBC development, but its underlying mechanisms are not well understood. MethodsHuman specimens were collected from Shengjing Hospital of China Medical University. Single-cell isolation and sequencing were conducted on cells from four GBC and four gallbladder adenomatous lesions (GBA) samples, and the raw gene expression matrices were analyzed using R software with the Seurat package. This included cell type annotation, differential gene expression analysis, functional enrichment, and gene set score calculation. Additional analyses such as protein-protein interaction network, immune infiltrate analysis, high-dimensional weighted gene co-expression network analysis, and cell-cell communication analysis were also performed. ResultsThe study revealed that epithelial-mesenchymal transition (EMT) plays a key role in the malignant transformation of epithelial cells from GBA to GBC. The immune landscape of GBC is predominantly immunosuppressive compared to the inflammatory environment within GBA. A specific subset of fibroblasts with extracellular matrix remodeling capabilities appears to be a major driver of the TME differences between GBC and GBA, potentially acting through COL1A2-mediated cell communication. DiscussionThis work highlights the distinct roles of various cell types in the TME of GBA and GBC, and emphasizes the importance of understanding the mechanisms of malignant transformation from adenomatous lesion to carcinoma in the gallbladder. The findings pave the way for further research into the mechanisms underlying the adenoma-carcinoma sequence.